Sub-cellular In-situ Characterization of Ferritin(iron) in a Rodent Model of Spinal Cord Injury - A. R. Blissett (Nature Portfolio, 2018)
Abstract Iron (Fe) is an essential metal involved in a wide spectrum of physiological functions. Sub-cellular characterization of the size, composition, and distribution of ferritin(iron) can provide valuable information on iron storage and transport in health and disease. In this study we employ magnetic force microscopy (MFM), transmission electron microscopy (TEM), and electron energy loss spectroscopy (EELS) to characterize differences in ferritin(iron) distribution and composition across injured and non-injured tissues by employing a rodent model of spinal cord injury (SCI). Our biophysical and ultrastructural analyses provide novel insights into iron distribution which are not obtained by routine biochemical stains. In particular, ferritin(iron) rich lysosomes revealed increased heterogeneity in MFM signal from tissues of SCI animals. Ultrastructural analysis using TEM elucidated that both cytosolic and lysosomal ferritin(iron) density was increased in the injured (spinal cord) and non-injured (spleen) tissues of SCI as compared to naïve animals. In-situ EELs analysis revealed that ferritin(iron) was primarily in Fe3+ oxidation state in both naïve and SCI animal tissues. The insights provided by this study and the approaches utilized here can be applied broadly to other systemic problems involving iron regulation or to understand the fate of exogenously delivered iron-oxide nanoparticles.